The Leadership Of Bundo Kanduang - Husna, Novriani; Erniwati, Erniwati (Alifah Health Science Symposium Proceeding, 2024)
Minangkabau is the largest tribe in Indonesia with a matrilineal kinship system refers to the tracing of kinship through the female line. In a matrilineal society, each person is identified their mother's lineage, and this can involve the inheritance of property and titles. It is a system in which ancestral descent is traced through maternal instead of paternal lines. Minangkabau customs regulate the order of society both individually, in groups and socially. Bundo kanduang is an informal leader for all women and their children and grandchildren in a tribe. All decisions must be discussed with him. Without permission from Bundo Kanduang, all plans cannot be implemented. Bundo Kanduang is the holder of inheritance in Minang Kabau. Bundo Kanduang is a traditional Minangkabau institution in West Sumatra, Indonesia. It is a matrilineal society where inheritance of the family property is passed to the youngest daughter. The Minangkabau culture of West Sumatra exhibits matrilineal succession, where only females are eligible to inherit.Women are more skilled at managing finances than men. matrilineality is a system of tracing kinship through the female line, and it can have significant implications for inheritance and leadership succession in various societies. Bundo Kanduang in West Sumatra, Indonesia example of a traditional institution that follows matrilineal succession, where the youngest daughter inherits the family property. The research method was carried out using library research. This research aims to determine women's leadership in Minang Kabau with the responsibilities assigned to them are expected to understand the nature of wise leadership.